2009
DOI: 10.1523/jneurosci.3256-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Musical Experience Limits the Degradative Effects of Background Noise on the Neural Processing of Sound

Abstract: Musicians have lifelong experience parsing melodies from background harmonies, which can be considered a process analogous to speech perception in noise. To investigate the effect of musical experience on the neural representation of speech-in-noise, we compared subcortical neurophysiological responses to speech in quiet and noise in a group of highly trained musicians and nonmusician controls. Musicians were found to have a more robust subcortical representation of the acoustic stimulus in the presence of noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

33
380
5
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(439 citation statements)
references
References 68 publications
33
380
5
7
Order By: Relevance
“…Moreover, we did not find that our violinist cohort -who spent significantly greater time in ensembles (see ST 2) -performed any better than our pianist cohort. These results contrast with previous reports of enhanced musician performance under the demands of competing speech (Parbery-Clark et al, 2009a, 2009b, 2011Strait et al, 2012b), sources of informational masking (Oxenham et al, 2003; see footnote 10), backward masking (Strait et al, 2010), and detection of auditory objects (Zendel & Alain, 2009. Our findings also contrast with previous evidence that specific expertise with ensemble settings benefits selective attention to spatially segregated sounds (Nager et al, 2003).…”
Section: Auditory Scene Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, we did not find that our violinist cohort -who spent significantly greater time in ensembles (see ST 2) -performed any better than our pianist cohort. These results contrast with previous reports of enhanced musician performance under the demands of competing speech (Parbery-Clark et al, 2009a, 2009b, 2011Strait et al, 2012b), sources of informational masking (Oxenham et al, 2003; see footnote 10), backward masking (Strait et al, 2010), and detection of auditory objects (Zendel & Alain, 2009. Our findings also contrast with previous evidence that specific expertise with ensemble settings benefits selective attention to spatially segregated sounds (Nager et al, 2003).…”
Section: Auditory Scene Analysiscontrasting
confidence: 99%
“…Schneider et al (2002) found enhanced early MEG component responses (N19m and P30m) in professional and amateur musicians compared to non-musicians (presumably reflecting contributions from auditory cortex generators). A variety of studies by Kraus and colleagues (e.g., Parbery-Clark et al, 2011;2009a;Strait et al 2012a;Skoe & Kraus, 2013) 7. Since the present experimental battery was 3+ hours in duration, we were not able to assess fullscale IQ for each participant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…É importante citar ainda, que a estruturação temporal para execução deste teste é adquirida a partir dos 7 anos, e que no decorrer do desenvolvimento as crianças adquirem a possibilidade de estruturar conjuntos sempre mais longos e complexos (Stambak, 1968 (Blundell et al, 2007;Ho et al, 2003;Parbery-Clark et al, 2009;Peretz & Zatorre, 2005;Rauscher & Zupan, 2000;Williamson et al, 2006).…”
Section: Discussionunclassified
“…These enhancements extend to the subcortical auditory system, with musicians showing responses to sound that are faster (55, 57-61), are degraded less by background noise (32, 61), represent speech formant structure more robustly (32,(62)(63)(64). differentiate speech sounds to a greater extent (65-67), track stimulus pitch more accurately (68, 69), and are more consistent across trials (59, 70).…”
mentioning
confidence: 99%